Relationship between neutropenia caused by nanoliposomal irinotecan/fluorouracil/leucovorin and treatment outcomes in the NAPOLEON-2 study (NN-2301) - Tomonori Araki; Yuki Sonoda; Mototsugu Shimokawa; Taiga Otsuka; Kohei Hayashi; Takuya Honda; Kazuhiko Nakao; Taro Shibuki; Junichi Nakazawa; Shiho Arima; Keisuke Miwa; Yoshinobu Okabe; et al. (Scientific Reports)
Abstract The relationship between nanoliposomal irinotecan/fluorouracil/leucovorin (NFF) treatment outcomes and neutropenia in patients with pancreatic cancer has not been thoroughly examined. Thus, we conducted a retrospective analysis of data from patients with pancreatic cancer who were treated with NFF to investigate this relationship. Neutropenia was assessed according to the Common Terminology Criteria for Adverse Events across three cutoffs: A (grade 0 versus grade 1–4), B (grades 0–1 versus 2–4), and C (grades 0–2 versus 3–4). The primary endpoint was overall survival (OS), and the secondary endpoints were overall response rate, progression-free survival (PFS), and relative dose intensity. Of the 161 patients, 93, 8, 22, 30, and 8 patients had neutropenia of grades 0, 1, 2, 3, and 4, respectively. The overall response rates differed significantly at cutoff C (p = 0.02), with the odds ratio for cutoff C being the highest, followed by cutoffs B and A. Significant differences in OS were observed at cutoffs A (hazard ratio [HR], 0.65; 95% confidence interval [CI], 0.44–0.94; p = 0.02) and B (HR, 0.63; 95% CI, 0.43–0.92, p = 0.02). Similarly, PFS showed significant differences at cutoffs A and B (p < 0.01). NFF-induced neutropenia can be a useful prognostic factor for patients with pancreatic cancer.